The effective increase in atomic scale disorder by doping and superconductivity in Ca3Rh4Sn13. (15th October 2018) - Ślebarski, A; Zajdel, P; Fijałkowski, M; Maśka, M M; Witas, P; Goraus, J; Fang, Y; Arnold, D C; Maple, M B
Abstract: A comprehensive study of the electronic structure, thermodynamic and electrical transport properties reveals the existence of inhomogeneous superconductivity due to structural disorder in Ca3 Rh4 Sn13 doped with La (Ca3− x La x Rh4 Sn13 ) or Ce (Ca3− x Ce x Rh4 Sn13 ) with superconducting critical temperatures T c ⋆ higher than those ( T c ) observed in the parent compounds. The T  −  x diagrams and the entropy S ( x ) T isotherms document well the relation between the degree of atomic disorder and separation of the high-temperature T c ⋆ and T c -bulk phases. In these dirty superconductors, with the mean free path much smaller than the coherence length, the Werthamer–Helfand–Hohenber theoretical model does not fit well the H c 2 ( T ) data. We demonstrate that this discrepancy can result from the presence of strong inhomogeneity or from two-band superconductivity in these systems. Both the approaches very well describe the H  −  T dependencies, but the present results as well as our previous studies give stronger arguments for the scenario based on the presence of nanoscopic inhomogeneity of the superconducting state. A comparative study of La-doped and Ce-doped Ca3 Rh4 Sn13 showed that in the disordered Ca3− x Ce x Rh4 Sn13 alloys the presence of spin-glass effects is the cause of the additional increase of T c ⋆ in respect to the critical temperatures of disordered Ca3− x La x Rh4 Sn13 . We also revisited the nature of structural phase transition at T ⋆ ∼ 130 ÷ 170 K and documented that there might be another precursor transition at higher temperatures. Raman spectroscopy and thermodynamic properties suggest that this structural transition may be associated with a CDW-type instability.